Plasma proteins and psoriatic arthritis: a proteome-wide Mendelian randomization study - Zhao, Heran; Zhou, Yi; Wang, Ziyan; Zhang, Xuan; Chen, Leilei; Hong, Zhinan (Frontiers in Immunology, 2024)
Background: Previous epidemiological studies have identified a correlation between serum protein levels and Psoriatic Arthritis (PsA). However, the precise nature of this relationship remains 2 uncertain. Therefore, our objective was to assess whether genetically determined circulating levels of serum proteins are associated with the risk of PsA, utilizing the Mendelian randomization (MR) approach.Methods: A two-sample MR analysis was conducted to evaluate the causal role of proteins in PsA. The exposure data for plasma proteins were obtained from a large-scale genome-wide association study (GWAS) conducted within the UK Biobank Pharma Proteomics Project, which encompassed 2,923 unique plasma proteins. The outcome data for PsA were sourced from the FinnGen study, a large-scale genomics initiative, comprising 3,537 cases and 262,844 controls.Additionally, colocalization analysis, Phenome-wide MR analysis, and candidate drug prediction were employed to identify potential causal circulating proteins and novel drug targets.We thoroughly assessed the association between 1,837 plasma proteins and PsA and found that seven proteins were associated with PsA. An inverse association of Interleukin-10 (IL-10) with PsA risk was observed [odds ratio (OR), 0.45, 95% confidence interval (CI), 0.28 to 0.70, PFDR=0.072]. Additionally, Apolipoprotein F (APOF) has a positive effect on PsA risk (OR=2.08, 95% CI, 1.51 to 2.86, PFDR= 0.005). Subsequently, we found strong evidence indicating that IL-10 and APOF were colocalized with PsA associations (PP.H4 = 0.834 for IL-10 and PP.H4 = 0.900 for APOF). Phenome-wide association analysis suggested that these two proteins may have dual effects on other clinical traits (PFDR<0.1) Conclusions: Our study identified 7 plasma proteins that were associated with PsA risk and provided new insights into the etiology of PsA. Further experimental and clinical studies are needed to evaluate the utility and efficacy of these candidates to ascertain the current findings.